2019
DOI: 10.2147/ppa.s187907
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient preferences for glucagon-like peptide-1 receptor&ndash;agonist treatment attributes</p>

Abstract: Purpose The importance of patient-centered care in the management of type 2 diabetes mellitus (T2DM) is widely advocated. Understanding the attributes of T2DM medications important to patients is thus essential for effective management, in order to limit disease progression. This literature review aimed to identify studies comparing patient preferences, based on process and outcome attributes, between GLP1-receptor agonist (RA) profiles and between GLP1 RA and insulin profiles. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Due to differences in nature and characteristics of the disease, the results may not represent the preferences of patients with other types of chronic diseases. Although prior DCEs [44][45][46][47][48] made conclusions that were similar to ours in terms of the relative importance of technology attributes regarding benefits and risks. Future studies need to enrol patients with other diseases and conduct subgroup analyses to identify variations in patients' preferences across different types of diseases.…”
Section: Strengths and Limitationssupporting
confidence: 75%
See 1 more Smart Citation
“…Due to differences in nature and characteristics of the disease, the results may not represent the preferences of patients with other types of chronic diseases. Although prior DCEs [44][45][46][47][48] made conclusions that were similar to ours in terms of the relative importance of technology attributes regarding benefits and risks. Future studies need to enrol patients with other diseases and conduct subgroup analyses to identify variations in patients' preferences across different types of diseases.…”
Section: Strengths and Limitationssupporting
confidence: 75%
“…Comparison with other studies Our findings of patients valuing the effectiveness and safety of medical technologies were consistent with the results by prior studies from other countries which aimed to investigate patients' preferences for the treatment of chronic diseases. [44][45][46][47][48] Our study confirmed that new technologies that could increase health benefits and minimise potential risks were preferred by patients.…”
Section: Summary Of the Findingssupporting
confidence: 70%
“…A growing body of literature has examined patient preferences among glucagon‐like peptide‐1 (GLP‐1) receptor agonists, which are often recommended for glycaemic control in patients with T2D . Medications in this class have been shown to have efficacy for lowering HbA1c with a low risk of hypoglycaemia and a potential benefit of weight loss .…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] Attributes of the injection device and procedures that have been shown to contribute to patient preference include needle handling requirements, steps for preparing the injection device, dose frequency and overall ease of use. 10,[39][40][41][42] The dulaglutide and semaglutide injection devices have been compared in a previous study in which preferences were based on descriptions of the devices with images from the device instructions for use, rather than actual experience of using the devices. 43 The primary objective of the current study was to examine preference between the dulaglutide and semaglutide injection devices after participants had been trained to inject with both devices and then used them to administer injections into an injection pad.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal adherence and persistence across the GLP-1RA class may be attributed to a variety of factors of importance to both patients and prescribers, including frequency of injections, administration device, needle size, efficacy, gastrointestinal side effects, and safety [106], as well as the more general consideration of affordability [107]. Although the variation across this class does allow for individualization of treatment for people with T2D, prescribers are faced with the challenge of familiarizing themselves with the dosing regimens and devices for several agents, with limited time and resources to educate patients on the correct administration and titration of these medications [68,108].…”
Section: Therapeutic Adherence and Persistence With Injectable Glp-1rasmentioning
confidence: 99%